Proceedings of the Sixth International Conference on Learning Analytics &Amp; Knowledge - LAK '16 2016
DOI: 10.1145/2883851.2883885
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing educational content in classrooms using Bayesian knowledge tracing

Abstract: Despite the prevalence of e-learning systems in schools, most of today's systems do not personalize educational data to the individual needs of each student. This paper proposes a new algorithm for sequencing questions to students that is empirically shown to lead to better performance and engagement in real schools when compared to a baseline approach. It is based on using knowledge tracing to model students' skill acquisition over time, and to select questions that advance the student's learning within the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 16 publications
0
20
0
4
Order By: Relevance
“…The results from Section 2 give us reason to pause. More convincing advances are provided by David et al [14], and the already discussed Liu and Koedinger [30]. These two papers back up their computational validation with user trials that demonstrate improved learning outcomes for students using the new tool over a comparable baseline.…”
Section: What Is An Improvement?mentioning
confidence: 94%
“…The results from Section 2 give us reason to pause. More convincing advances are provided by David et al [14], and the already discussed Liu and Koedinger [30]. These two papers back up their computational validation with user trials that demonstrate improved learning outcomes for students using the new tool over a comparable baseline.…”
Section: What Is An Improvement?mentioning
confidence: 94%
“…A learner can demonstrate the acquisition of knowledge and skills as a product of their learning process. Most key studies in this category operationalize affected learning through grades or test scores or scores [29], [33]- [35], [37], [49], [50], [53], [54], [57], [61], [63], [67]- [70], [74]- [76], which is a direct assessment of learning as performance on a task (e.g., an exam or final test) [94]. Although grades may seem to be a direct operational definition, this is debatable.…”
Section: Analysis and Refinement Of The Classification Schemementioning
confidence: 99%
“…The students were randomly divided into 3 cohorts: (1) MAPLE Sequencing: Students in this group received questioned sequenced by the MAPLE algorithm when practicing with the system. (2) YBKT Sequencing 1 : students in this group received questioned sequenced by the Bayesian Knowledge Trace based algorithm proposed by Ben David et al [6]. This sequencing approach always chooses the next question from the available skill set in a deterministic manner.…”
Section: Deployment and Evaluation In The Classroommentioning
confidence: 99%
“…We then implemented MAPLE in the wild in an existing e-learning system in a school with 7th grade students. MAPLE's performance was compared to two other sequencing algorithms already implemented in the e-learning system: an approach that sequenced questions according to educational expert guidelines and a state of the art Bayesian Knowledge Tracing based algorithm [6]. We found that our proposed approach showed promising results compared to the existing educational expert approach and the BKT based approach.…”
Section: Introductionmentioning
confidence: 96%